The Lament for the Missing Girl in Byzantine Hagiography Focused on Women - Narro, Angel (Vox Patrum, 2026)
This article examines the hagiographic motif of the lament for a missing girl, tracing its origins and evolution from the Acts of Paul and Thecla through various Byzantine hagiographic texts, including both the Life of Eugenia and its metaphrastic version, the Life of Apollinaria, and the Life of Euphrosyne. It explores how this motif, initially secondary in the APTh, becomes central in later texts and demonstrates direct textual and thematic connections between these works. The analysis highlights the continuity and adaptation of literary and rhetorical elements, emphasizing their significance in the development of Byzantine hagiography.